2001
DOI: 10.1080/036107301750074051
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress and Coping Resource Availability as Predictors of Life Satisfaction in Young, Middle-Aged, and Older Adults

Abstract: Global satisfaction with life across three age groups (18 to 40 years, 41 to 65 years, and 66 years and above) was investigated. Multiple regressions were computed to examine the separate and joint effects of perceived stress and coping resource availability upon life satisfaction across the three age groups (N = 189). Age differences in perceived stress, coping resource availability, and life satisfaction, were also investigated. Results of this cross-sectional investigation indicated that self-appraisal meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
1
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(57 citation statements)
references
References 30 publications
10
43
1
3
Order By: Relevance
“…The emerging findings on the relationship between gratitude and well-being in this study are in the life with previous research (e.g., Emmons & McCullough, 2003;Kong et al, 2015;McCullough et al, 2002;Wood et al, 2008aWood et al, , 2008b. The results are also compatible with previous studies on the relationship between stress and satisfaction with life (e.g., Hamarat et al, 2001;Lee et al, 2016;Simons et al, 2002;Wood et al, 2008b) and stress and gratitude (e.g., Lin, 2015;Wood et al, 2008b).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The emerging findings on the relationship between gratitude and well-being in this study are in the life with previous research (e.g., Emmons & McCullough, 2003;Kong et al, 2015;McCullough et al, 2002;Wood et al, 2008aWood et al, , 2008b. The results are also compatible with previous studies on the relationship between stress and satisfaction with life (e.g., Hamarat et al, 2001;Lee et al, 2016;Simons et al, 2002;Wood et al, 2008b) and stress and gratitude (e.g., Lin, 2015;Wood et al, 2008b).…”
Section: Discussionsupporting
confidence: 83%
“…Findings revealed that perceived stress is a significant predictor of life satisfaction (Hamarat et al, 2001). Perceived stress was found positively linked with increased symptoms of minor psychiatric disorders and postnatal depression (Chaaya et al, 2010).…”
Section: Mediating Role Of Perceived Stressmentioning
confidence: 81%
See 2 more Smart Citations
“…In daily life, this may translate into experiencing better momentary affective states, less stress, and showing less indication of physiological stress. Although evidence from daily life is sparse, broadly consistent with this view, adults with higher levels of global life satisfaction report lower levels of perceived life stress (Hamarat et al, 2001). Second, that global life satisfaction may buffer against the negative effects of stress (Suldo & Huebner, 2004;Veenhoven, 2008).…”
Section: Global Life Satisfaction and Daily Healthmentioning
confidence: 63%